Gyroid‐Nanostructured All‐Solid Polymer Films Combining High H+ Conductivity with Low H2 Permeability. Issue 12 (22nd June 2021) - Kobayashi, Tsubasa; Li, Ya‐xin; Hirota, Yuichiro; Maekawa, Asako; Nishiyama, Norikazu; Zeng, Xiang‐bing; Ichikawa, Takahiro
Abstract : Front Cover : In article number 2100115 by Takahiro Ichikawa, Xiangbing Zeng, and co‐workers, gyroid‐nanostructured polymer films, having multi‐layered H2 gas barriers and a 3D continuous proton conduction pathway, are created from specially‐designed bicontinuous cubic liquidcrystalline monomers. They show high proton conductivity of the order of 10 −1 S cm −1 and extremely low H2 gas permeability of the order of 10 −15 mol m m −2 s −1 Pa −1 .